Pengaruh Musik Klasik Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi Di RSUD Rupit - Nanda Permata Sari; Mariza Arfianti; Sulastri Sulastri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hypertension is a condition caused by the interaction of many risk factors. Rupit Regional General Hospital is located in Rupit Subdistrict, Muratara Regency, South Sumatra Province. Based on a preliminary survey conducted by the author, data from the hospital’s health services department revealed that there are still a significant number of elderly patients suffering from hypertension at Rupit Regional General Hospital, and this number continues to rise each year alongside other conditions such as diabetes mellitus, gout, and osteoporosis. This is why the author chose to conduct this study at that location, Rupit Regional General Hospital, Muratara Regency, South Sumatra Province. This study employed a quantitative research design using a quasi-experimental method with a pre- and post-test approach without a control group. The study was conducted at Rupit Regional General Hospital from July to August 2025, involving 23 elderly respondents with hypertension who were outpatients at the hospital. SPSS Version 25.0.0 was used for data analysis. The respondents, all of whom were 60 years of age or older and thus classified as elderly, numbered 23 (100%); among them, 9 (40%) were men and 14 (60%) were women. The blood pressure of elderly patients at Rupit Regional General Hospital before receiving classical music therapy had an average systolic reading of 152.17 mmHg and a diastolic reading of 93.87 mmHg. The minimum systolic range was 140–160 mmHg, and the minimum diastolic range was 90–99 mmHg. The blood pressure of elderly patients at Rupit Regional General Hospital after receiving classical music therapy had an average systolic value of 123.61 mmHg and a diastolic value of 77.87 mmHg. The minimum systolic value was 110 mmHg and the minimum diastolic value was 70 mmHg. The minimum systolic blood pressure is 110–130 mmHg, and the minimum diastolic blood pressure is 70–85 mmHg. Based on the data analyzed using SPSS as described above, it was concluded that there was a statistically significant effect on blood pressure reduction before and after classical music therapy was administered to elderly patients in the outpatient department at Rupit Regional General Hospital.